Localised delivery of quercetin by thermo-sensitive PLGA-PEG-PLGA hydrogels for the treatment of brachial plexus avulsion. Issue 1 (1st January 2020) - Huang, Chao; Fu, Chuan; Qi, Zhi-Ping; Guo, Wen-Lai; You, Di; Li, Rui; Zhu, Zhe
Abstract: Accumulating evidence indicates that oxidative stress and inflammation are implicated in brachial plexus avulsion (BPA). Quercetin has anti-inflammatory, anti-oxidant, anti-apoptotic, and neuroprotective properties. This study investigated the therapeutic efficacy of a temperature-sensitive poly(D, L-lactide-co-glycolide)-poly(ethylene-glycol)-poly(D, L-lactide-co-glycolide) (PLGA-PEG-PLGA) hydrogel sustained-release system of quercetin in BPA. In situ injections of the hydrogel loaded with different concentrations of quercetin were conducted in a rat model of BPA. Significantly reduced reactive oxygen species and interleukin-6 levels in the injured spinal cord 24 h post-surgery, increased number of anterior horn motor and functional neurons in the spinal cord 6 weeks post-surgery, thickened biceps muscle fibres and enlarged endplate area with clear structure, reduced demyelinated peripheral nerves, and significantly increased Terzis grooming test scores were found in the groups with 50 or 100 mg/mL quercetin-loaded hydrogels compared with the control and blank hydrogel groups. In conclusion, the temperature-sensitive quercetin loaded PLGA-PEG-PLGA hydrogel sustained-release system can alleviate oxidative damage and inflammation in the spinal cord, increase neuron survival rate, and promote nerve regeneration and motor function recovery in rats with early BPA. The findings suggest that this drug-loaded hydrogel has potential applications in the clinical treatment of BPA.